High-current relativistic electron beam focusing in plasma - Manuilenko, О.V.; Pashchenko, A.V.; Svichensky, V.G.; Zajtsev, B.V. (Вопросы атомной науки и техники, 2021)
The analysis of the envelope equation for high-current relativistic electron beam propagation in plasma in an external uniform magnetic field is presented. The envelope equation is obtained in a Hamiltonian form with an effective potential, which depends from electron beam and plasma parameters, and external magnetic field. Hamiltonian aproach allows fully analyze the behavior of the beam envelope as a function of the beam current, beam energy, plasma density and conductivity, as well as on the external magnetic field and the initial beam angular momentum.